Accounting for terrestrial and marine carbon sink enhancement - Marius Paschen; Felix Meier; Wilfried Rickels (Kiel Institute for the World Economy (IfW), 2022)
Any integration of extra carbon dioxide removal (CDR) via terrestrial or marine sink enhancement into climate policies requires accounting for their effectiveness in reducing atmospheric carbon concentration. Different accounting methods have been introduced to quantify the impacts of sink enhancements. Here, we provide a manual for the different accounting methods, accompanying the implementation of the accounting methods in a R-file which is free for download. Hence, the material allows applying the different accounting methods and for demonstration purposes we provide a numerical example.
Keywords: Q54; 330; Carbon Dioxide Removal; Temporary Carbon Storage; Carbon Sinks; Carbon Accounting